Asylum Courts, Transnational Petitioning, and Digital Dispersal in Africa. (June 2020) - Lawrance, Benjamin N.; Corcoran, Erin B.; Hooper, Louise
Abstract: Asylum court records are a potentially important evidentiary basis for postcolonial African history. Asylum-seeking is a contemporary transnational iteration of a rich African petitioning tradition. In the contemporary era, the digitization of court records, and their dispersal as a function of the shifting division of work between ministries, courts, and related bureaucracies, presents a challenge to researchers. Digital record keeping may improve accessibility, but only if researchers are familiar with the technology and archival methods and practices accompanying digitization.